Relationship between inter-arm blood pressure differences and future cardiovascular events in coronary artery disease. Issue 9 (September 2015) - Tokitsu, Takanori; Yamamoto, Eiichiro; Hirata, Yoshihiro; Fujisue, Koichiro; Sugamura, Koichi; Maeda, Hirofumi; Tsujita, Kenichi; Kaikita, Koichi; Hokimoto, Seiji; Sugiyama, Seigo; Ogawa, Hisao
<x xml:space="preserve">Abstract</x> Objective: Recent studies have shown that inter-arm blood pressure differences (IAD) may be a risk factor for cardiovascular events; however, none have addressed them in patients with coronary artery disease (CAD). Methods: We measured blood pressure bilaterally with the ankle brachial index (ABI) in 657 patients with suspected CAD and assessed the presence of CAD by coronary angiography, and the severity of coronary atherosclerosis with the Gensini score. Results: Mean IADs were significantly greater in risk factor matched patients with CAD than in those without it (P = 0.01), whereas Gensini scores were significantly greater in those with high IAD (≥10 mmHg) than in those with low-IAD (P = 0.01) according to cross-sectional analysis. Patients with high IAD had a significantly greater probability of cardiovascular events than those in whom it was low (log-rank test, P < 0.01, mean follow-up range; 827.3 ± 268.1 days). The presence of hypertension, ABI, usage of calcium channel blocker and high IAD were independent predictors of cardiovascular events according to longitudinal analysis (IAD; hazard ratio: 2.90, 95% confidence interval: 1.41–5.94, P < 0.01) in these patients. Patients with high IAD and peripheral artery disease had the highest Gensini scores according to cross-sectional analysis (P < 0.01) and highest probability of cardiovascular events according to longitudinal analysis (log-rank test, P < 0.001). Conclusion: IADs were increased in CAD patients and correlated with its severity. Greater than 10 mmHg of IAD was independently associated with future cardiovascular events. Assessing IAD by ABI measurement may facilitate risk stratification in CAD patients.